An interactive multimedia reading comprehension package (IMRCP) for knowledge and skills enhancement / Othman Ismail and Noraini Ahmand Basri - Ismail, Othman; Ahmand Basri, Noraini (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This project is based on an FRGS grant, to design, develop and produce an instructional material for the Interactive Multimedia Reading Comprehension Package (IMRCP).The project is geared towards developing reading comprehension skills for L2 and distance learners. With new cutting-edge technology, developing reading skills can be assisted tremendously. Ismail (2001) stated that computers in the classroom assist in teaching and learning. Ruiz, Mintzer and Leipzig (2006) found that learners using computer-based instruction learned more effectively, efficiently and demonstrated better retention. Today, interactive multimedia and web-based technologies have provided alternative means of acquiring the needed skills pertinent for effective language learning. In understanding a text, reading strategies deployed by the readers play a significant role. Levine, Ferenz and Reeves (2000) stated that the reading strategies include creating mental images, guessing intelligently, drawing linguistic schemata, drawing content schemata, translating from LI to L2 and predicting. Despite the technological innovations in the area of computer-mediated learning, not many e-materials are available off the shelves. If any, these materials are not tailored for the targeted learners or educators. These previous studies signal the need for a customized IMRCP to be developed and produced. This product can be made available to all educators with a very minimum cost; yet, the product contents can easily be modified and customized according to the educators' requirements.